SENI BATIK MEGAMENDUNG CIREBON DAN PENGARUHNYA TERHADAP SENI MODE DI INDONESIA - Menul Teguh Riyanti (Jurnal Dimensi Seni Rupa dan Desain, 2012)
AbstractBatik is one of Indonesia's cultural  heritage products. along with the times, many   batik   patterns  change,  functions  and  there  is  a  touch  of  other cultures. On  his general decoration I style batik following  forms of natural phenomena, or  objects  of even;day          experience.                          Example          is     the megamendung  of  batik   patterns   that   follow  the  natural   phenomenon, because the motive  in  the form of batik Cirebon cloud. Technique  done in two babaran. First at babar cloth with red, at batik again later dyed blue, and  even, sometimes  dyed  with  yellow color (tageran).  So would  happen crosses the color red, blue, black, and green with a white base, now  there is the color of the manufacturer or synthetic colors that enrich the color of the overcast   cloud  batik.  Fashion  art  at  this   time,   many   apply   batik   in everyday  clothing, formal  or  informal. Because batik  bet  is  interesting, unique and  have  artistic   value  of  the  image  height.   Presence  of  batik fashion design has been with the times  is expected to strengthen the textile and batik as an original Indonesian art and culture.  AbstrakBatik merupakan salah satu warisan produk  budaya Indonesia. Seiring dengan perkembangan zaman, batik banyak mengalami perubahan corak, fungsi serta terdapat sentuhan dari budaya lain. Pada umumnya ragam hias/corak batik mengikuti bentuk-bentuk gejala alam, atau benda-benda yang dialami sehari-hari, contohnya adalah corak batik mega mendung yang mengikuti gejala alam karena motifnya yang berbentuk awan. Teknik pembuatan batik Cirebon dikerjakan dalam dua kali babaran. Pertama-tama kain itu dibabar  dengan  warna  merah,  dibatik  lagi  kemudian  dicelup dengan warna biru bahkan kadang kala dicelup dengan warna kuning (tageran).  Demikian akan terjadi persilangan warna